공액고분자의 전기전도도와 열전출력 최적화를 위한 고효율 분자도핑공정 설계 연구 - 윤상은 (The Graduate School, Ajou University, 2024)
Conjugated polymers (CPs) are attracting attention as suitable materials for organic thermoelectric devices due to their process convenience, mechanical stability, biocompatibility, and eco-friendliness. However, compared to inorganic-based thermoelectric materials, conjugated polymers have significantly lower electrical properties, which limits the implementation of high-performance thermoelectric devices. To solve this problem, this thesis aimed to develop high-performance organic thermoelectric devices by improving the electrical conductivity of conjugated polymers through doping. The goal was to improve the electrical conductivity and thermoelectric performance of high-performance organic thermoelectric devices by focusing on the design, selection, and doping methods of CPs to enhance the doping efficiency. _x000D_ Chapter 1 provides a comprehensive overview of the essential properties of CPs, doping mechanisms, methods, and the effects of enhanced doping efficiency on the performance of organic thermoelectric devices._x000D_ Chapter 2 discusses strategies to increase doping efficiency through material-driven approaches, such as adjusting the bulkiness of the side chains of conjugated polymers to facilitate dopant diffusion and charge transport. Additionally, an examination of the effects of molecular weight on charge mobility and concentration post-doping. Comparative studies on the thermoelectric performance of polymers doped with various oxidizing agents, such as F4-TCNQ and AuCl3, are presented. Lastly, the selection of solvents for dopants is optimized to improve the dissolution and diffusion of dopants into CP thin films, thereby enhancing their electrical properties_x000D_ Chapter 3 presents systematic research on strategies to enhance doping efficiency from a process perspective. This chapter describes hybrid doping techniques that combine sequential and blend doping to maximize carrier concentration by doping all areas within CP thin films, thereby optimizing electrical conductivity and device performance. The chapter further introduces cascade doping, which involves sequential doping with different dopants to maximize charge concentration and improve electrical conductivity. Finally, solvent combination doping is investigated to optimize solvent properties, enhancing dopant diffusion efficiency after pristine film casting and achieving high-performance, highly conductive organic thermoelectric devices._x000D_ This thesis systematically optimizes materials and processes, deepening the understanding of the complex interplay between conjugated polymer design, doping processes, and thermoelectric properties. It presents a series of methodological advancements aimed at optimizing the performance of organic thermoelectric devices. These advanced methodologies are expected to significantly impact the development of organic thermoelectric energy conversion technologies.
학위논문(박사)--분자과학기술학과,2024. 8
Keywords: Cascade doping; Conjugated polymer; Doping method; Electrical conductivity; Hybrid doping; Molecular doping; Organic thermoelectric; Sequential doping; Solvent combination doping